Histories, politics, and cultural considerations in qualitative research - Notshulwana, Velile (PINS-Psychology in Society, 2022)
Nakray, Keerty, Alston, Margaret & Whittenburg, Kerri (2016). Social sciences research ethics for globalizing world: Interdisciplinary and cross-cultural perspective. Routledge. 332 pages. ISBN -13: 978-0-415-71622-2